African Elephant Specialist Group report/Rapport du Groupe des Specialistes des Éléphants d'Afrique - Dublin, Holly (Pachyderm, 2004)
Reviews recent AfESG activities and programme implementation including: publication (both hardcover and online) of the 2002 edition of the African Elephant Status Report (formerly the African Elephant Database); dissemination of the 'Guidelines for the in situ translocation of the African elephant for conservation purposes'; organization of the 6th meeting of the AfESG held in Namibia in December 2003; continuing development of national and subregional elephant conservation strategies; and, implementation of research and management projects in coordination with non-governmental agencies and national governments. Other points of interest include the 'vulnerable' listing of the African elephant is the 2004 Red List, maintenance and further development of the website (htt://iucn.org/afesg), and the compilation of reference materials. A troubling point of concern is the lack of core funding support beyond 2004.